Exploring Sales Models for College Student Entrepreneurship Projects - Zhu, Zhengxing (International Journal of Global Economics and Management, 2024)
College students have become a significant force in the entrepreneurial wave, thanks to the widespread availability of higher education and the in-depth implementation of innovation and entrepreneurship policies. The selection and implementation of product sales strategies are crucial to the survival and development of college student entrepreneurship projects. This paper explores diversified sales strategies suitable for such projects, aiming to provide valuable references for similar enterprises.